Investigation of inheritance of chronic inflammatory bowel diseases by complex segregation analysis. - Orholm, M (1993)
OBJECTIVE--To investigate the mode of inheritance of ulcerative colitis and Crohn's disease by complex segregation analysis. DESIGN--Cross sectional population based survey of familial occurrence of chronic inflammatory bowel disease. SETTING--Population of the Copenhagen county in 1987. SUBJECTS--662 patients in whom inflammatory bowel disease had been diagnosed before 1979, of whom 637 (96%) provided adequate information. Of 504 patients with ulcerative colitis, 54 had 77 relatives with ulcerative colitis and of 133 patients with Crohn's disease, five had seven relatives with Crohn's disease. MAIN OUTCOME MEASURES--Patterns of segregation of either disease as assessed by complex segregation analysis performed with the computer program POINTER. RESULTS--The analysis suggested that a major dominant gene with a penetrance of 0.20-0.26 is present in 9-13% of adult patients with ulcerative colitis. The analysis did not allow for other components in the familial aggregation. For Crohn's disease the best fitting model included a major recessive gene with complete penetrance, for which 7% of the patients are homozygous. However, this model was not significantly different from a multifactorial model. CONCLUSIONS--The segregation pattern indicates that a major dominant gene has a role in ulcerative colitis, and suggests that a major recessive gene has a role in Crohn's disease.